Origins of strength and plasticity in the precious metal based high-entropy alloy AuCuNiPdPt. (15th February 2020) - Thiel, F.; Geissler, D.; Nielsch, K.; Kauffmann, A.; Seils, S.; Heilmaier, M.; Utt, D.; Albe, K.; Motylenko, M.; Rafaja, D.; Freudenberger, J.
Highlights: The precious metal based High-Entropy Alloy (HEA) AuCuNiPdPt is of single phase fcc structure in the homogenised state. Decomposition occurs during annealing AuCuNiPdPt at intermediate temperatures. AuCuNiPdPt deforms by deformation twinning and dislocation slip at room temperature. AuCuNiPdPt shows a high yield strength of 820 MPa and a high yield ratio of 0.66 at room temperature as well as significant strain hardening during deformation. The strengthening mechanisms of AuCuNiPdPt are assessed. Graphical abstract: Abstract: The precious metal based High-Entropy Alloy (HEA) AuCuNiPdPt crystallises in a face-centred cubic structure and is single phase without chemical ordering after homogenisation. However, a decomposition is observed after annealing at intermediate temperatures. This HEA shows extended malleability during cold work up to a logarithmic deformation degree of φ = 2.42 . The yield strength ranges from 820 MPa in the recrystallised state to 1170 MPa when strain hardened by cold working with a logarithmic deformation degree of φ > 0.6. This work hardening behaviour is traced back to a steep increase in dislocation density as well as in deformation twinning occurring at low strain. The microstructure and the mechanical properties of AuCuNiPdPt are assessed in detail by various methods. EBSD and TEM analyses reveal mechanical twinning as an important deformation mechanism. The high strength in the recrystallised state is evaluated and found to originate predominantly upon solid solution strengthening.